What Covid-19 hath wrought and debt exit options: A note on deficit financing and public debt management - Dante B. Canlas (University of the Philippines, School of Economics (UPSE), 2020)
This paper opens up a study of deficit financing and management of the public debt in the context of the COVID-19 outbreak in the Philippines. Borrowings of the national government from the monetary authority and from domestic and international financial markets, as well as the options for exiting from the public debt enlarged by such borrowings are assessed. At this juncture, public spending to strengthen social safety nets for truly disadvantaged families and firms are imperatives, but taxation that relieves big corporations and shifts to households and small firms the recovery of foregone corporate income taxes through burdensome indirect taxes must be shunned. Meanwhile, growing out of the public debt through sound monetary policy and structural reforms that embrace rise in total factor productivity is the least painful option to exit out of the newly expanded public debt.
Keywords: E5; O4; 330; COVID-19; public debt management; deficit financing; Philippines